2020
DOI: 10.3390/foods9101465
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sea Salt, Dry Sourdough and Fermented Sugar as Sodium Chloride Replacers on Rheological Behavior of Wheat Flour Dough

Abstract: The aim of this study was to investigate the effects of formulation factors, sea salt (SS), dry sourdough (SD) and fermented sugar (FS) as sodium chloride replacers in wheat flour on dough mixing, extension, pasting and fermentation rheological properties, evaluated by Farinograph, Extensograph, Amylograph and Rheofermentometer devices. With regard to mixing and extension properties, SS and FS presented a strengthening effect, whereas SD presented a weakening one. SS and FS presented a positive effect on dough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Regarding its effect on fermentation process, it seems that levels usually used in bread inhibit yeast activity, decreasing the gas formed during the fermentation process [ 124 ]. In bakery products NaCl leads to good sensory properties, increases the shelf life of the products, improves the loaf volume of bread and leads to a uniform crumb texture and brown colour [ 125 , 126 ].…”
Section: Methods To Reduce the Acrylamide Content In Bakery Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding its effect on fermentation process, it seems that levels usually used in bread inhibit yeast activity, decreasing the gas formed during the fermentation process [ 124 ]. In bakery products NaCl leads to good sensory properties, increases the shelf life of the products, improves the loaf volume of bread and leads to a uniform crumb texture and brown colour [ 125 , 126 ].…”
Section: Methods To Reduce the Acrylamide Content In Bakery Productsmentioning
confidence: 99%
“…However, even if the use of sourdough in bread reduces the AA level its technological effect on bread making must be taken into account. Different studies have reported that sourdough addition in bread recipes has a weakning effect on wheat flour dough [ 124 , 126 , 147 ]. This may not favour the quality of bakery products obtained from weak quality wheat flour used bread making [ 148 , 149 ].…”
Section: Methods To Reduce the Acrylamide Content In Bakery Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact indicates that dough becomes less stable and weaker when SD is added to wheat flour. A weakening effect of SD addition on dough mixing properties has previously been reported by other researchers [26][27][28]. This may be due to the fact that the addition of SD to wheat flour may lead to a hydrolytic intensification of the protein and starch degradation.…”
Section: Effect Of Dry Sourdough On Mixolab Rheological Parametersmentioning
confidence: 65%
“…The SD addition led to a slightly acidic dough, with a pH value of around 5.7, an optimum level for the amylase enzyme in the dough samples with high levels of SD incorporated in the wheat flour. The optimal temperature and pH for amylase activity led to an increase in their activity and therefore to a decrease in dough viscosity [28]. Consequently, the maximum torque-measure of starch gelatinization C3 value decreased with the increase in the levels of SD added to the wheat flour.…”
Section: Effect Of Dry Sourdough On Mixolab Rheological Parametersmentioning
confidence: 97%